Where do we go from here? Past present and future logistics of the British Army - Moore, David M.; Antill, Peter D. (Common Services Establishment, 2000)
This paper will focus on the logistics approach as used by the British Armed Forces during the Cold War, what it is today, and what future operations may involve. It will also look at certain aspects of commercial logistics practice to see what could be applied to the British Armed Forces.